Ambiguity Degrees of Courtesy in Trial: Ethical and Legal Norms, Legal Reasoning in Judicial Decisions - Helmi, Muhammad Ishar; Pujiyono, Pujiyono; Zada, Khamami; Encep, Encep (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
Courtesy reasons are the basis for the legal reasoning of mitigation, as stated in the decision. Courtesy reasons only happen in one case. The Criminal Code explains the aggravating and mitigating circumstances of a sentence that is not considered decent in a conference. Explicitly, the word courtesy is not a reason to lighten the sentence. Article 197, paragraph 1, letter f of the Criminal Procedure Code contains the words